2015
DOI: 10.1109/tpwrs.2014.2329324
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Network Optimal Power Flow: Uniqueness and Algorithms

Abstract: Abstract-The optimal power flow (OPF) problem minimizes the power loss in an electrical network by optimizing the voltage and power delivered at the network buses, and is a nonconvex problem that is generally hard to solve. By leveraging a recent development on the zero duality gap of OPF, we propose a second-order cone programming convex relaxation of the resistive network OPF, and study the uniqueness of the optimal solution using differential topology especially the Poincare-Hopf Index Theorem. We character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…However, by observing that ½ AE are matrices with nonpositive off-diagonal elements, the authors in [14], [15] show that (9) can be solved exactly by (10). Furthermore, it has been shown that this tight relaxation result also implies that the Lagrange duality gap of (9) is zero, and (9) can also be solved exactly by a second order cone programming relaxation [12], [13], [22]. A more general result that applies to the AC (alternating current) OPF problem can be found in [12], [13], [15].…”
Section: Preliminaries On Convex Relaxation Of Static Opfmentioning
confidence: 99%
See 4 more Smart Citations
“…However, by observing that ½ AE are matrices with nonpositive off-diagonal elements, the authors in [14], [15] show that (9) can be solved exactly by (10). Furthermore, it has been shown that this tight relaxation result also implies that the Lagrange duality gap of (9) is zero, and (9) can also be solved exactly by a second order cone programming relaxation [12], [13], [22]. A more general result that applies to the AC (alternating current) OPF problem can be found in [12], [13], [15].…”
Section: Preliminaries On Convex Relaxation Of Static Opfmentioning
confidence: 99%
“…In our recent work [22], we leverage this zero duality gap property to design low-complexity distributed algorithms to solve (9) directly instead of solving the SDP convex relaxation in (10) with a centralized SDP solver (e.g., interior-point method). In fact, the optimal solution of (9) can be unique (for different network topologies, e.g., line, radial and mesh networks).…”
Section: Preliminaries On Convex Relaxation Of Static Opfmentioning
confidence: 99%
See 3 more Smart Citations